Ethics as a System Forming Factor of the Students’ Education in the Process of Professional Training of the Future Lawyers and Managers - Denyshchyk, Oleksii (Pedagogical Discourse, 2013)
The attention in the article is paid to the grounding of objective necessity and historic grounding of the further humanization of educational process in high school by means of strengthening of the role of ethics as a system forming factor of the students’ education.